Phytochemical Screening of Murraya paniculata L. Leaf Extract Using Methanol, N-Hexane and Ethyl Acetate as Anticholesterol Candidates - Aini, Qurratu; Manja, Manja; Rizki, Cut Novrita; Suwarniati, Suwarniati; Fairuz Yusoff, Siti (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
This study aims to identify the secondary metabolite content and active compounds in plant extracts through phytochemical screening and Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Phytochemical tests revealed the presence of flavonoids, alkaloids, tannins, and terpenoids, which are known for their biological activities including antioxidant and anticholesterol properties. GC-MS analysis identified 21 compounds, with dominant constituents including Phytol, 8-(2,3-Dihydroxy-3-methylbutyl)-7-methoxy-2H-chromen-2-one, and Murrayatin. Among these, Phytol was identified as the primary candidate for anticholesterol activity, supported by literature indicating its role in inhibiting cholesterol biosynthesis. These findings suggest that the extract has potential as a natural anticholesterol agent, although further pharmacological studies are needed to confirm its specific bioactivity. Skrining Fitokimia Ekstrak Daun Murraya paniculata L. Menggunakan Metanol, N-Heksana dan Etil Asetat sebagai Kandidat Antikolesterol ABSTRAK: Penelitian ini bertujuan untuk mengidentifikasi kandungan senyawa metabolit sekunder serta senyawa aktif dalam ekstrak tumbuhan menggunakan uji fitokimia dan analisis Gas Chromatography-Mass Spectrometry (GC-MS). Uji fitokimia menunjukkan adanya senyawa flavonoid, alkaloid, tanin, dan terpenoid yang diketahui memiliki aktivitas biologis, termasuk sebagai antioksidan dan antikolesterol. Analisis GC-MS mengungkapkan 21 senyawa, dengan senyawa dominan antara lain Phytol, 8-(2,3-Dihydroxy-3-methylbutyl)-7-methoxy-2H-chromen-2-one, dan Murrayatin. Di antara senyawa tersebut, Phytol diidentifikasi sebagai kandidat utama senyawa antikolesterol berdasarkan referensi ilmiah yang mendukung aktivitasnya dalam menghambat biosintesis kolesterol. Hasil ini menunjukkan bahwa ekstrak tumbuhan ini memiliki potensi sebagai agen antikolesterol alami, namun diperlukan uji farmakologis lanjutan untuk mengonfirmasi aktivitas tersebut secara lebih spesifik.